Corporate criminal liability– overcoming selected obstacles of application of the concept - Baltiņa, Karīna (Riga Graduate School of Law, 2018)
Criminal liability and criminal sanctions have always been distinguished from civil and administrative ones by implying moral condemnation. Upon the emergence of criminal offences committed in the context of business entities, the concept of corporate criminal liability was introduced. Due to the criminal law’s original application only to individuals, the concepts supporting criminal liability have been developed on the basis of natural persons’ characteristics. Despite that, the recognition and application of corporate criminal liability have been increasing. This thesis examines what measures states have taken in order to overcome the obstacles arising from the application of the concept of corporate criminal liability. The results of the thesis indicate that the implementation of the doctrines supporting corporate criminal liability within the legal systems of the states have served as a major basis for overcoming the obstacle of the establishment of corporate mens rea. Besides the states being able to overcome the particular obstacle, they have interpreted doctrines in various ways in that way adjusting concept to their legal systems. However, obstacles delaying effective application of the doctrines cannot be considered as fully resolved. Therefore, the further development of the corporate criminal liability must be sought. Even more, regarding some of the member states of European Union – the adopted approaches seem as a tool for complying with European Union law, not an actual interest in holding legal persons criminally liable. Finally, in regard to states that have taken the particular matter seriously – the tendency of introducing elements that deviate from the original concept of criminal liability, although not in obvious way, can be found.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Criminal law; Criminal liability